2018
DOI: 10.1016/j.maturitas.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and diabetes: EMAS clinical guide

Abstract: Introduction: Whether menopause increases the risk of type 2 diabetes mellitus (T2DM) independently of ageing has been a matter of debate. Controversy also exists about the benefits and risks of menopausal hormone therapy (MHT) in women with T2DM. Aims: To summarise the evidence on 1) the effect of menopause on metabolic parameters and the risk of T2DM, 2) the effect of T2DM on age at menopause, 3) the effect of MHT on the risk of T2DM, and 4) the management of postmenopausal women with T2DM. Materials and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 65 publications
0
53
0
10
Order By: Relevance
“…This leads to serious pathophysiological changes such as depression, anxiety, sleep disorders, hot flashes, night sweats, and menstrual disorders [2]. In addition, the risk of metabolic abnormalities in menopausal women increases significantly [3][4][5][6]. For example, a cross-sectional and longitudinal analysis has shown that plasma intermediate-density lipoprotein (IDL) and LDL levels are higher in menopausal women than in women of childbearing age [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to serious pathophysiological changes such as depression, anxiety, sleep disorders, hot flashes, night sweats, and menstrual disorders [2]. In addition, the risk of metabolic abnormalities in menopausal women increases significantly [3][4][5][6]. For example, a cross-sectional and longitudinal analysis has shown that plasma intermediate-density lipoprotein (IDL) and LDL levels are higher in menopausal women than in women of childbearing age [3].…”
mentioning
confidence: 99%
“…Another prospective population study has shown that menopause and aging are independently correlated with body mass index (BMI) increase [4]. Insulin resistance in menopausal women is found to increase the incidence of type II diabetes (T2DM) [5], and significantly increase the risk of metabolic syndromes (MetS) [6]. Thus, the decline in estrogen level in menopause is closely related to metabolic abnormalities.…”
mentioning
confidence: 99%
“…5 However, this increased risk is of a similar magnitude to the risk of breast cancer for women who are overweight, or drinking one or two units of alcohol each night. 1 Frustratingly, despite this evidence, only around 10% of women in the UK are currently taking HRT. 10 Although some women choose not to take HRT or cannot take it for medical reasons, a large proportion of women are declined a prescription for HRT for no valid medical reason.…”
Section: The Risks Of Hrtmentioning
confidence: 99%
“…However, the effects of the menopause often have a negative impact on women's wellbeing and quality of life, and are frequently underestimated by noth women and their doctors. Furthermore, the low estrogen levels and other biological changes that occur in menopausal women are also associated with an increased risk of cardiovascular disease, osteoporosis, type 2 diabetes, 1 and dementia. 2 Around 75% of menopausal women experience symptoms, with around onethird of these experiencing severe symptoms which are having a negative effect on their lives, both at home and at work.…”
mentioning
confidence: 99%
See 1 more Smart Citation